Endoscopic Management of Peri-Pancreatic Collections - David Keith Swartz; Jorge Obando (Gastroenterology Research and Practice)
Endotherapy of peripancreatic fluid collections is an increasing utilized procedure in interventional endoscopy. The aim of this paper is to provide a general overview of the topic, highlighting the indications, technique, and important management issues relating to endoscopic management of the various forms of peri-pancreatic fluid collections.